Застосування ігрових механік в комп’ютерних відеоіграх - Часовська, А. О. (ХНУРЕ, 2023)
This work examines the history of development and structure of game mechanics. Game mechanics are used to describe how players interact with the rules, as well as more formal properties of the game, such as game objectives, player actions and strategies, and game states. The process of deconstructing mechanics begins with the search for reference games. The problems that arise during the reproduction of this mechanic were studied and the methods of their solution were considered. On the basis of the conducted analysis, the approbation of the considered methods of deconstruction of game mechanics was carried out in the work
Keywords: розробка ігор; відеоігра